TINGKAT KETERGANTUNGAN NELAYAN GILLNETDI KARANGSONG, KABUPATEN INDRAMAYU TERHADAP SUMBERDAYA IKAN - Solikhin, Iin; Wiyono, Eko Sri; Solihin, Akhmad (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Fishermen have a high level dependency on fish resources. Therefore, it is necessary to make a job diversification as an alternative income. However, to diversify the job, it is necessary to analyze the dependency level of fishermen on fish resources. The purpose of this research are (1) to describe gillnet fisheries in PPI Karangsong, (2) to analyze the dependency level of fishermen in PPI Karangsong on fish resources. Using cryterias of number of families, time allocation, income, and expenses dependency level of fishermen were calculated using Multi Cryteria Analysis (MCA). The result of this stydy showed that gillnet fishermen in Karangsong coastal fishing port is dominated by gillnet 0-10 GT group. Gillnet ship which less than 25 GT is still using ice to preserve the fish, while the bigger ship (≥ 25 GT) already using freezer. Dependency level of fishermen who operated gillnet < 20 GT is higher than gillnet > 20 GT.